2003
DOI: 10.1021/jm030091l
|View full text |Cite
|
Sign up to set email alerts
|

1-[[(3-Hydroxy-1-adamantyl)amino]acetyl]-2-cyano-(S)-pyrrolidine:  A Potent, Selective, and Orally Bioavailable Dipeptidyl Peptidase IV Inhibitor with Antihyperglycemic Properties

Abstract: Dipeptidyl peptidase IV (DPP-IV) inhibition has the potential to become a valuable therapy for type 2 diabetes. The synthesis and structure-activity relationship of a new DPP-IV inhibitor class, N-substituted-glycyl-2-cyanopyrrolidines, are described as well as the path that led from clinical development compound 1-[2-[5-cyanopyridin-2-yl)amino]ethylamino]acetyl-2-cyano-(S)-pyrrolidine (NVP-DPP728, 8c) to its follow-up, 1-[[(3-hydroxy-1-adamantyl) amino]acetyl]-2-cyano-(S)-pyrrolidine (NVP-LAF237, 12j). The ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
397
2
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 595 publications
(409 citation statements)
references
References 63 publications
5
397
2
5
Order By: Relevance
“…Previously we have shown that vildagliptin (also called LAF-237) improves glucose tolerance in high-fat fed glucose intolerant mice (25). Vildagliptin also has been shown to augment the insulin response to oral glucose and glucose tolerance in obese Zucker rats (20) and to improve glucose tolerance in ob/ob mice (26) and Zucker diabetic fatty rats (27). The antidiabetic action of vildagliptin relies on increased concentrations of active (intact) GLP-1, since DPP-4 inhibition prevents the inactivation of the incretin hormone (1-3).…”
Section: Discussionmentioning
confidence: 99%
“…Previously we have shown that vildagliptin (also called LAF-237) improves glucose tolerance in high-fat fed glucose intolerant mice (25). Vildagliptin also has been shown to augment the insulin response to oral glucose and glucose tolerance in obese Zucker rats (20) and to improve glucose tolerance in ob/ob mice (26) and Zucker diabetic fatty rats (27). The antidiabetic action of vildagliptin relies on increased concentrations of active (intact) GLP-1, since DPP-4 inhibition prevents the inactivation of the incretin hormone (1-3).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, none of the evaluated substituents was able to improve FAP potency significantly, with substituents in the 2-and 3-position of the quinoline ring as in compounds 19−24, having a clearly negative effect on this parameter. Identifying the factors that cause this effect is not evident from these six analogues, but both steric (19,22, and 23) and electronic (20,21, and 24, with an increased electron density in the pyridine ring compared to 7) factors seem to be contributive. Remarkably, PREP-affinity is affected in a more intricate manner by these substitution types: the negative effect of 3-hydroxylation in 20 and 24 significantly contrasts with the influence of a 2-hydroxyl functionality in 21.…”
Section: * S Supporting Informationmentioning
confidence: 92%
“…Moreover, several adamantanebased drugs are currently employed as important medications against malaria infections [7], central nervous disorders [8][9][10], hyperglycaemia [11] and drug-resistant TB strain infections [12]. In addition, thiourea derivatives were reported to display marked antitumor [13], anti-HIV [14], antimalarial [15] and antimicrobial [16] activities.…”
Section: Discussionmentioning
confidence: 99%